Proceedings of the 20th Annual International Conference on Mobile Systems, Applications and Services 2022
DOI: 10.1145/3498361.3538935
|View full text |Cite
|
Sign up to set email alerts
|

EarHealth

Abstract: With the aging of the population and the long-time wearing of earphones, hearing health has gradually emerged as a worldwide health issue. Early detection of hearing health conditions would greatly reduce potential risks with timely medical intervention. This study proposes an earphone-based ear condition monitoring system, named EarHealth, which is low-cost, non-invasive, and easily usable in daily life. It can detect three major hearing health conditions: ruptured eardrum, earwax buildup and blockage, and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Other smartphone-enabled innovative avenues to diagnose middle ear conditions exist. For example, several studies have shown that acoustic reflectometry may replace tympanometry for middle ear fluid detection 32,33 . Two studies recorded and analyzed echoes from a device linked to a smartphone and showed promising performance compared with traditional diagnostic tools.…”
Section: Discussionmentioning
confidence: 99%
“…Other smartphone-enabled innovative avenues to diagnose middle ear conditions exist. For example, several studies have shown that acoustic reflectometry may replace tympanometry for middle ear fluid detection 32,33 . Two studies recorded and analyzed echoes from a device linked to a smartphone and showed promising performance compared with traditional diagnostic tools.…”
Section: Discussionmentioning
confidence: 99%